El trabajo de las mujeres en la pequeña minería - Farfán Durán, María Verónica (2018)
This research analyzes how the work of the Jancheras Women of the Independent Women Worker’s Association “Las Águilas”, is inserted in the mining production, understood not only as a work, but as a structure of symbolic, political, economic and cultural relations, which influence the whole life in Camilo Ponce Enríquez. The demand of male labor is very high in the area, while for women, there are no greater wage-labour opportunities unless they have a professional title, which is why most of them are in charge of domestic work. This affects to households that have a woman as the provider, which is the case of the majority of jancheras women in Camilo Ponce Enríquez. Mining as a labour system, masculinizes the work-spaces, affecting to families whose provider, is not a man. The ethnographic method is used, and the main tools are: observation, participant observation and open interviews. The main interlocutor of the project is Mrs. Eliana Paltán, president of the Jancheras Women's Association "Las Águilas". First, I make a description of the jancheras’s work from the perspective of the association’s members and their president. In a second section, the information is confronted with the concept of Sexual Division of Labour and its implications. Finally, I talk about the relevance of the concept of "Nuclear Family" in the miner town and the impacts of the entertainment trade in the families.